2015
DOI: 10.1371/journal.pone.0145291
|View full text |Cite
|
Sign up to set email alerts
|

Delphinidin Inhibits Tumor Growth by Acting on VEGF Signalling in Endothelial Cells

Abstract: The vasculoprotective properties of delphinidin are driven mainly by its action on endothelial cells. Moreover, delphinidin displays anti-angiogenic properties in both in vitro and in vivo angiogenesis models and thereby might prevent the development of tumors associated with excessive vascularization. This study was aimed to test the effect of delphinidin on melanoma-induced tumor growth with emphasis on its molecular mechanism on endothelial cells. Delphinidin treatment significantly decreased in vivo tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Furthermore, several other flavonoids, such as galangin, myricetin, chrysin, hispidulin, nobiletin, delphinidin, barbigerone, eupatorin or wogonin, were found to inhibit the VEGF signaling pathway either due to a direct effect on VEGF/VEGFR2 or via modulation of VEGFR2-mediated downstream signaling [ 54 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Effect Of Polyphenols On Angiogenesismentioning
confidence: 99%
“…Furthermore, several other flavonoids, such as galangin, myricetin, chrysin, hispidulin, nobiletin, delphinidin, barbigerone, eupatorin or wogonin, were found to inhibit the VEGF signaling pathway either due to a direct effect on VEGF/VEGFR2 or via modulation of VEGFR2-mediated downstream signaling [ 54 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Effect Of Polyphenols On Angiogenesismentioning
confidence: 99%
“…To support the hypothesis of the involvement of angiogenesis in atherosclerosis, Qiu et al showed that arterial regions with higher shear stress also exhibit an elevated number of intraplaque microvessels, characterized by abnormal endothelial cells, in particular with intracytoplasmatic vacuoles and leukocyte infiltration that could lead to rupture-prone plaque formation [39]. In cancer research, multiple in vitro studies demonstrated the anti-angiogenic effect of anthocyanins, in particular concerning delphinidin, as a potential chemopreventive agent [40][41][42]. We found that Peo-3-glc, Pet-3-glc and their metabolites (VA and MetGA) reduced the levels of VEGF, corroborating the hypothesis of a protective mechanism of action through which these compounds inhibit angiogenesis within the atheroma, therefore reducing atherosclerotic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the glycosylated B-ring in the structure of anthocyanins are highly effective regarding their antioxidant activity, where ortho-hydroxylation and methoxylation significantly increase the antioxidant activity [ 292 ]. Several in vitro studies have reported the antioxidant effect of anthocyanins when conducted on the colon [ 293 , 294 ], endothelial [ 295 ], liver [ 296 ], breast [ 226 , 239 ], leukemic [ 123 ] and keratinocytes [ 297 ], cervical [ 280 ] and melanoma [ 124 ] cell lines. In these studies, anthocyanins have shown to exhibit multiple anticarcinogenic effects from scavenging reactive oxygen species to reducing cell proliferation, from stimulating the expression of Phase II detoxification enzymes to inhibiting mutagenesis by environmental toxins and carcinogenesis, among others.…”
Section: Anthocyanins’ Potential For Health Benefitsmentioning
confidence: 99%